TANGGUNG JAWAB HUKUM TERHADAP PEMBERI INFORMASI PALSU YANG MENGANCAM KESELAMTAN PENERBANGAN BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 2009 - Lailatul Uzni; Amad Sudiro (Jurnal Hukum Adigama, 2019)
Air transportation is something that is currently very loved by almost every society, this is because air transportation has a fast, up-to-date and efficient mobilization, but transportation with this airplane mode if it is not accompanied by qualified safety rules will have a negative impact on every individual who uses it. hence from that society and government must be more wise in enforcing existing legal rules for the sake of creating security and safety in the flight itself, because flight is one of the safest transportation according to existing data, therefore in order to maintain the good name of air transportation, especially aviation, there is a need for compliance with any existing regulations that have been determined by the government, cannot be arbitrary. in flight it upholds the meaning of safety and security for every passenger and cabin crew, because it is the priority of every airline safety is the dead price for each mode of transportation. so that air transport modes, especially airlines, are getting better, then we need to work from ourselves in safeguarding every word and behavior that can endanger the safety and security of aviation.